Analisis Dampak Lingkungan dan Keekonomian Pembangkit Listrik Tenaga Co-firing Biomassa dan Baru bara sebagai Upaya Bauran Energi Terbarukan - Palupi, Dhiyanti Nawang; Sundari, Sri; Syahtaria, M. Ikhwan; Sianipar, Leo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Steam power plants are the largest contributor to carbon emissions in Indonesia. Utilizing biomass fuel through co-firing technology is one way to reduce carbon dioxide emissions. As part of an effort to increase the use of renewable energy, this study will assess the economic and environmental effects of co-firing biomass and coal power plants. This study uses a descriptive method of analysis of literature studies. The research results show that the continuous use of coal can lead to extinction. According to the data, the energy potential of biomass reaches 32.6 GW, with a new utilization of 1,895.7 MW, or around 5.8%. It takes more than 9 million tons of biomass every year to support the application of co-firing technology in 52 steam power plants in Indonesia. Various sources of biomass have the potential to support the application of co-firing technology. To achieve the target of 23 percent of the new renewable energy mix in 2025, the supply of biomass is very helpful. In addition to being able to increase its contribution to the renewable energy mix, the application of co-firing can also help the growth of the people's economy or circular economy. Keywords: Coal, Biomass, Co-firing, Economy, Environment